Design of a chip based lock-in amplifier for low frequency measurements - Abhishikta (IISER Mohali, 2022)
When measuring weak signals, lock-in amplifiers (LIAs) are often employed to enhance noise-to-signal ratios. Constructing and testing an appropriately constructed LIA provides a wonderful chance for us to gain knowledge about the theory, construction, and applica- tions of LIA. We can get an understanding of time-dependent behaviour and a variety of components, ranging from resistors (R) and capacitors (C) to packed microchips such as de- modulators and phase shifters. We present the design and performance characteristics of a two-channel (Vx, Vy) balanced modulator/demodulator based LIA (AD630). The LIA has resistor-capacitor (RC) high-pass and low-pass filters, as well as different op-amp circuits and a phase shifter.
Keywords: chip based; amplifier; frequency measurements